The effect of chitosan in preventing the adverse effects of aging on the germination and seedling development of corn plant - Zulkadir, Zulkadir (Revista Ciência Agronômica, 2021)
In this study, in which the effect of chitosan coating on the aging process of a seed was investigated, the rapid agingtimes applied did not have a negative effect on the Gmax value of the seeds. Therefore, the effect of chitosan and aging treatments onseed germination and germination time at this stage could not be observed. In the examinations for seedling development, the valuesobtained on the 14 th, 30 th and 60 th days were determined to be between 9.558-13.910 cm, 12.868-21.410 cm and 34.458- 66.243 cmfor root length; 1.55-2.49 cm, 3.198-4.770 cm and 11,843-18,442 cm for seedling length; 0.173-0.280 g, 0.690-1.570 g and 2.508-5.903 g forfresh root weight; 0.170-0.240 g, 0.653-1.608 g and 3.413-16.273 g for fresh shoot weight; 0.018-0.030 g, 0.090-0.170 g and 0.248-0.553 g fordry root weight; 0.018-0.020 g, 0.083-0.188 g and 0.338-1.543 g for dry shoot weight; 0.150-0.250%, 0.600-1.418% and 2.163-5.358%for root moisture content; 0.150-0.220%, 0.570-1.420% and 3.075-14.728% for shoot moisture content, respectively. EC values weredetermined as 0.640-0.930 µS cm-1g-1 on the 30th day and 0.230-0.641 µS cm-1g-1 on the 60th day. Considering the general effects ofthe applications, the best results were obtained in A2B2 applications in the 14-day period, A1B1 in the 30-day period and A2B2in the 60-day period. According to these results, it was observed that chitosan periodically increased the seedling growth in the maizeplant. More research is needed on the effects of chitosan applications on germination and seedling growth.